Factors associated with knowledge on healthy community, empowers nation (KOSPEN) and its implementation among community health volunteers in Kulim district, 2017 (ada comment di pdf) - Sondaram, Navindra Kumar (2017)
Introduction: The increasing burden of Non-Communicable Diseases and their prevalence has led Ministry of Health (MOH) Malaysia to introduce a community empowerment program “Komuniti Sihat, Perkasa Negara” acronymed as KOSPEN in July 2013. Thirty thousand community health volunteers have been trained nationwide up to May 2015.